The Development of Social Skills for Children Aged 4-5 Years - Sakinah Siregar (Jurnal Scientia, 2023)
This study aims to find out about the development of social skills in children aged 4-5 years to achieve social interactions that are in accordance with the development of preschool children. This research is a qualitative study using a literature review approach. Based on some of these definitions, it can be concluded that what is meant by social skills is having a sense of concern for others, being able to establish communication and social interaction, working together, having social responsibility, and controlling aggression so as to obtain a harmonious adaptation in their environment. family, school environment and even community environment framework can be applied in practice. Explain what the implications are for communication and social interaction.